The Implications of the Heir Determination on Heirs Died at the Time the Stipulation is Filed - Vista, Pranedya Alinea; Nugraheni, Destri Budi (Jurnal Bina Mulia Hukum, 2024)
Proof of being an heir is required in the process of transferring the heir's inheritance. One proof of being an heir is the determination of the heir, who has the right to inherit by a religious court. However, there are disparities in the three judges decisions in determining heirs who have died when the decision is submitted. This article aims to analyze the basis for the judge's considerations in giving different positions to heirs who have died at the time the decision is requested, and the implications for the transfer of inheritance. This research is normative legal research by analyzing secondary data in the form of court decisions and supplemented by interviews with various sources. The research results were then analyzed qualitatively.The research results show that the judge relied on Article 174 KHI in determining heirs who had died when the application was submitted as heirs. This is appropriate, because it is in accordance with the concept of munashakah in jurisprudence, namely handingover the share of an heir who has died to the person who inherited it because he died after the testator and before the distribution of inheritance was carried out. Another determination does not determine an heir who has died as an heir because the heir is revealed by the heir's biological child. The implication of determining an heir for an heir who has died is that it is necessary to determine another heir for the heir who has died.This is because there are conditions that are not met for the inheritance process, namely the identity (KTP) of the heir who has died.died because there are requirements that are not fulfilled for the process of inheritance assets transfer.